Enhancing the Islamic education in Kurikulum Merdeka through international benchmarking: A transdisciplinary study - Rahmat Ryadhush Shalihin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to investigate the application of benchmarking in Indonesian education and offer solutions to develop benchmarking within the Islamic education curriculum within Kurikulum Merdeka, Indonesia's national curriculum. The goal is to improve the quality of Islamic education nationally and internationally. The study method is descriptive qualitative research with a transdisciplinary perspective, drawing on relevant literature sources from Islamic education, applied sciences, and business disciplines. The results suggest that further development of international benchmarking in internal, external, strategic, process, performance, general, and functional benchmarking is necessary to develop the Islamic education curriculum. It should be based on collaboration and global standards and involve a transdisciplinary approach. The study highlights the need for benchmarking to move beyond a formality in national education standards and to be integrated into Islamic education to improve education quality and compete globally.